Design of Educational Learning Management Cloud Process with Blockchain 4.0 based E-Portfolio - Purnama, Suryari; Aini, Qurotul; Rahardja, Untung; Santoso, Nuke Puji Lestari; Millah, Shofiyul (Universitas Pendidikan Ganesha, 2021)
The development of technology in education has produced many innovations to support the learning process. The large variety of learning media is the digital competence of education, which is very much needed in higher education . However, from several universities, there are still many that do not have adequate digital competence. This study uses a survey method that will be calculated quantitatively through a Likert Scale calculation. The design of this cooperative education management system uses E-Portfolio Integration stored in cloud computing based on Blockchain technology. The Blockchain process will be helpful as a literary platform for researchers who will start research on Blockchain technology for digital education so that the results of digital competence cannot be taken over by third parties and are transparent, and this is the solution to the problems in this research. Based on the study results, it can be seen that the Student-Centered iLearning Blockchain (SCi-B) with E-Portfolio is supported by Blockchain technology that can meet the needs of universities and improve cooperative education on digital competence.